Sediment fingerprinting: source classification - Vercruysse, Kim; Grabowski, Robert C. (Cranfield University, 2018)
This data is related to a research project using sediment fingerprinting based on Diffuse Reflectance Infrared Fourier Transform Spectrometry (DRIFTS) to estimate sediment source contributions to suspended sediment in rivers. The research took place in the River Aire catchment, United Kingdom. The data was collected between 2014 and 2017.Two types of data are available:1. Suspended sediment concentrations during high-flow events (SuspendedSedimentConcentration_RiverAire.csc). Samples were collected with a depth-integrating suspended sediment sampler from the side of the river at Brewery Wharf in the city center of Leeds (dates are indicated)2. Diffuse Reflectance Infrared Fourier Transform Spectrometry (DRIFTS) spectra of sediment samples Type of samples: - suspended sediment, - bed sediment, - sediment sources (*),- experimental mixtures of sediment source samples. Each type of sample is included in a separate .CSV file (**)(*) Sample IDs: CR, LR, MR (samples from eroding riverbanks in coals, limestone and millstone area respectively). CU, LU, MU (samples from uncultivated grassland soils in coals, limestone and millstone area respectively). U (urban street dust samples). Numbers 1-2-3 represent sub samples taken within one square meter.(**) First row of the columns in all DRIFTS files represent the wavelength (micrometer-1) ranging between 3799 and 651
Keywords: Suspended Sediment Concentration'; 'DRIFTS study'; 'Geomorphology and Regolith and Landscape Evolution'; 'Hydrology'; 'Physical Geography'; 'Sedimentology'; 'Soil Science'